Science, Technology, and Innovation in Uganda : Recommendations for Policy and Action - Brar, Sukhdeep (World Bank, 2012)
Between 2006 and 2010 the World Bank sought to unmask the role of science, technology, and innovation in Ugandan industry. This report presents insights from this research based on case studies of six sectors: agriculture, health, energy, information and communication technology (ICT), transport, and logistics. Based on more than 80 interviews cutting across Uganda's small and medium-sized enterprises, universities, and government entities, the report's findings are intended to offer the government and its partners in industry increased clarity about how better to harness science, technology, and innovation to propel the economy. Enabling implementation of the recent Uganda national science, technology, and innovation policy is a parallel goal of the report. The policy articulates the government's intent to foster research and development that builds the human capital that Uganda requires for a knowledge-based economy. The case studies from which this report's recommendations are drawn depict a diverse range of experiences across industrial sectors in terms of generating, applying, and adapting science and technology to contribute to Uganda's development. Despite the relatively small size of the country's investments in science and technology, the past 20 years have seen considerable advances in building capacity in science and technology, developing related institutions and human resources, advancing collaboration and communication, and expanding the base of available knowledge. But given Uganda's limited investments in science and technology, policies should prioritize near-term investments that benefit key sectors. This report identifies those near-term investments as well as longer-term ones (three to five years in the future).